PERKEMBANGAN SYAIR JANTURAN JEJER PERTAMA PERKELIRAN WAYANG KULIT GAYA SURAKARTA - Timbul Subagya (Paraguna, 2018)
Wayang kulit, performance  art  in the  culture of Javanese society,  developed as  a traditional  art that  navigates  competition in the  era  of globalization.  No wonder  the  Javanese  people  love  it  very   much  as  a  part  of their   lives. Although this  art  is  a  binding tradition,  it appeared dynamic,  evolved and changed  over   time.   This   article   wrote   about  the  phenomenon  of change especially in the  use ofjanturan literature.  The  dalang sang janturan as  a narrative that  told  the  situation in  the  wayang history.  Every generation of dalang  in Surakarta,  used different  versions ofpoetry.